2007
DOI: 10.1001/archpedi.161.8.730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a School-Based, Early Childhood Intervention on Adult Health and Well-being

Abstract: Participation in a school-based intervention beginning in preschool was associated with a wide range of positive outcomes. Findings provide evidence that established early education programs can have enduring effects on general well-being into adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
253
3
13

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(284 citation statements)
references
References 31 publications
13
253
3
13
Order By: Relevance
“…Jablonska et al found that the risk for hospital admission due to self-harm increased steeply in a stepwise manner with decreasing grade point averages from the last compulsory school year, Hazard Ratio 6.7 in those with the lowest level of grade point averages compared to those with the highest [5]. Along the same line, an educational (and family service) program from preschool to third grade was associated with a number of positive psychosocial outcomes, including a trend for lower rate of depressive symptoms, at 24 years of age [6].…”
Section: Introductionmentioning
confidence: 85%
“…Jablonska et al found that the risk for hospital admission due to self-harm increased steeply in a stepwise manner with decreasing grade point averages from the last compulsory school year, Hazard Ratio 6.7 in those with the lowest level of grade point averages compared to those with the highest [5]. Along the same line, an educational (and family service) program from preschool to third grade was associated with a number of positive psychosocial outcomes, including a trend for lower rate of depressive symptoms, at 24 years of age [6].…”
Section: Introductionmentioning
confidence: 85%
“…All other interventions targeted both parents and children to simultaneously enhance protection and reduce family and individual risks. Examples include enhanced education services for primarily low-income, very young children to improve their cognitive, language, and socialcognitive skills; [48][49][50] and interventions that strengthen parenting skills, parent-child communication, and affective relationships. These include universal (eg, the Strengthening Families Program for Parents and Youth 10-14 28,72,73 and the Computer-Based Intervention 54,55 ), selective (eg, the New Beginnings Program 56 ), and indicated programmes (eg, Functional Family Therapy 74 ).…”
Section: The Science Of Preventionmentioning
confidence: 99%
“…26 The program shares characteristics with other pre-school interventions that appear to have shown lasting benefits. 27,28 However, the project as a whole proved difficult to evaluate as it lacked a control group and differed in content from centre to centre. 26,29 Further, such studies are rare: only 13% of the prevention studies in a metanalysis were routine interventions among which the authors retrieved only one randomized trial.…”
mentioning
confidence: 99%